2015
DOI: 10.1038/nmeth.3624
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding-domain fusions enhance the targeting range and precision of Cas9

Abstract: The CRISPR-Cas9 system is commonly employed in biomedical research; however, the precision of Cas9 is sub-optimal for gene therapy applications that involve editing a large population of cells. Variations on the standard Cas9 system have yielded improvements in the precision of targeted DNA cleavage, but often restrict the range of targetable sequences. It remains unclear whether these variants can limit lesions to a single site within the human genome over a large cohort of treated cells. Here, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 63 publications
4
114
0
2
Order By: Relevance
“…RFLP and T7E1 experiments showed GUIDE-seq tag incorporation and overall mutagenesis rates to be slightly lower in HEK293 cells compared with U2OS cells (Supplementary Figs. 6a-6c), consistent with previous studies 26 . GUIDE-seq analysis with each of the three crRNAs and AsCpf1 or LbCpf1 in HEK293 cells identified a similar number of off-target sites to what was observed in corresponding experiments performed in U2OS cells (Figs.…”
Section: Ratios Of Dsodn Incorporation Efficiency To Overall Modificasupporting
confidence: 93%
See 1 more Smart Citation
“…RFLP and T7E1 experiments showed GUIDE-seq tag incorporation and overall mutagenesis rates to be slightly lower in HEK293 cells compared with U2OS cells (Supplementary Figs. 6a-6c), consistent with previous studies 26 . GUIDE-seq analysis with each of the three crRNAs and AsCpf1 or LbCpf1 in HEK293 cells identified a similar number of off-target sites to what was observed in corresponding experiments performed in U2OS cells (Figs.…”
Section: Ratios Of Dsodn Incorporation Efficiency To Overall Modificasupporting
confidence: 93%
“…GUIDE-seq has been previously used by our group and others to identify off-target cleavage sites of wild-type and engineered Cas9 nucleases 12,16,[23][24][25][26][27] based on the capture of an end-protected, double-stranded oligodeoxynucleotide (dsODN) into nucleaseinduced breaks in living cells with subsequent amplification and identification of adjacent genomic sequences by deep sequencing. We assessed dsODN incorporation at 11 of the 22 matched sites we had shown above can be targeted by all three nucleases ( Fig.…”
mentioning
confidence: 99%
“…I-TevI fusions to Cas9 variants with altered PAM specificities (40,41), or fusion to other Cas9 homologs (42), could similarly broaden the targeting range. It remains to be seen whether the I-TevI nuclease and linker domains mitigate Cas9 off-target effects, as observed with the chimeric ZF-Cas9 and FokI-dCas9 fusions (9,11,43). One striking result from our study was that TevCas9 generates defined length deletions of 33-36 bp in HEK293 with minimal DNA end processing.…”
Section: Discussionmentioning
confidence: 68%
“…In a clever marriage of genome-editing platforms, the FokI cleavage domain has even been fused to an inactivated Cas9 variant to generate hybrid nucleases that require protein dimerization for DNA cleavage (Guilinger et al 2014b;Tsai et al 2014), theoretically increasing CRISPRCas9 specificity. Similarly, fusing Cas9 to DNA-binding domains has also proven effective at improving its specificity (Bolukbasi et al 2015). Finally, several studies have recently showed that protein engineering can broadly enhance Cas9 specificity (Kleinstiver et al 2016;Slaymaker et al 2016) and even alter its PAM requirements (Kleinstiver et al 2015), the latter having the potential to enable creation of customized variants of Cas9 for allele-specific gene editing, although Cas9 orthologs Esvelt et al 2013;Hou et al 2013;Ran et al 2015) or alternative CRISPR systems (Zetsche et al 2015a) with unique PAM specificities have been uncovered in nature.…”
Section: Crispr-cas9mentioning
confidence: 99%